Performance Analysis of Adaptive Defense Schemes (ADS) in Protection and Reliability Systems of Electric Power Transmission Systems - Tri Ismail Ricky Ramadhan; Solly Aryza; Muhammad Erpandi Dalimunthe (Sean Institute, 2026)
The reliability of the electric power transmission system is a crucial factor in ensuring the continuity of electrical energy distribution to customers. Disturbances in the transmission system can cause significant technical and economic losses. Therefore, the application of Adaptive Defense Schemes (ADS) was developed as an effort to improve the performance of the protection system and the reliability of the electric power transmission system. This study aims to analyze the performance of ADS on the Barikin-Tanjung bay line electric power transmission system and evaluate its technical and economic effectiveness. The disturbance data used include the number of disturbances, the duration of disturbances, and Energy Not Supplied (ENS) during the period 2015–2022, which is divided into the pre-implementation period of ADS (2015–2018) and post-implementation period of ADS (2019–2022). The Autoregressive Integrated Moving Average (ARIMA) method is used to analyze the characteristics of time series data and forecast disturbances in the period 2023–2026. The results of the analysis show that the implementation of ADS is able to reduce the number of disturbances, the duration of disturbances, and the ENS value significantly in the post-implementation period. The selected ARIMA models, namely ARIMA (2,1,1) for the number of disturbances, ARIMA (3,1,1) for the duration of disturbances, and ARIMA (2,1,1) for ENS, produced stable predictions with residuals without significant autocorrelation. In addition, the results of the economic analysis showed that the implementation of ADS was able to reduce the company's potential losses by more than 50% compared to the scenario without ADS. Thus, ADS has proven effective in improving the reliability of the electric power transmission system and is worthy of being recommended for implementation in other transmission lines with high levels of vulnerability.